2017
DOI: 10.1021/acs.jpclett.7b00479
|View full text |Cite
|
Sign up to set email alerts
|

Determining Key Local Vibrations in the Relaxation of Molecular Spin Qubits and Single-Molecule Magnets

Abstract: Herein we develop a simple first-principles methodology to determine the modulation that vibrations exert on spin energy levels, a key for the rational design of high-temperature molecular spin qubits and single-molecule magnets. This methodology is demonstrated by applying it to [Cu(mnt)2] 2-(mnt 2-= 1,2-dicyanoethylene-1,2-dithiolate), a highly coherent complex, using DFT to calculate the normal vibrational modes and wave-function based theory calculations to estimate the spin energy level structure. By theo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
170
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(177 citation statements)
references
References 51 publications
1
170
0
6
Order By: Relevance
“…[25,26] The direct process is favored in the low-T region, whereas the Orbach process is dominant at higher T. This agreesw ith the role of anharmonic phonons described by Sessoli et al, [46] but differs from the source of the phonon-spin interactions. The Pd-Gdv ibrational modes, which represents aunique metal-metal interaction intrinsic to the coordination geometry of 1,i sb elieved to be the origin of the phonon [47] rather than the crystal lattice, which Sessoli and coworkers [20] have reported for potential V-based molecular qubits. Although there are two relaxation peaks for 1,o nly one relaxation peak was observed for 3 and the frozen solutions.…”
Section: Dynamic Magneticpropertiesmentioning
confidence: 99%
“…[25,26] The direct process is favored in the low-T region, whereas the Orbach process is dominant at higher T. This agreesw ith the role of anharmonic phonons described by Sessoli et al, [46] but differs from the source of the phonon-spin interactions. The Pd-Gdv ibrational modes, which represents aunique metal-metal interaction intrinsic to the coordination geometry of 1,i sb elieved to be the origin of the phonon [47] rather than the crystal lattice, which Sessoli and coworkers [20] have reported for potential V-based molecular qubits. Although there are two relaxation peaks for 1,o nly one relaxation peak was observed for 3 and the frozen solutions.…”
Section: Dynamic Magneticpropertiesmentioning
confidence: 99%
“…[34,36] In order to correctly account for the vibrational properties of solid state systems, where intermolecular interactions become relevant, DFT calculations are performed in the crystal phase, in contrast to previous studies where the gas phase was taken into consideration. [34] The quality of our computed vibrational properties is ascertained by IR vibrational spectroscopy in the THz range. The information extracted from DFT and post Hartee-Fock methods together provide a fingerprint description of the interaction between vibrations and magnetism, and directly correlate to the structure of each compound.…”
Section: Introductionmentioning
confidence: 99%
“…They found that spin-phonon relaxationv ia anharmonic phonons may also result in Arrheniusb ehavior,b ut with the U eff corresponding to half of the vibrational frequency.F urthermore, other research teams analyzed the locality of the spin-phonon interaction and concluded that molecular vibrations spatially localized close to the metal center usually have the strongest contribution to the spin relaxation. [17,19] These findings show that the Debye model is oversimplified for the analysiso f spin-phonon relaxation in molecular magnets [20] and an analysis of the real vibrational spectra may give better insighti nto the relaxation mechanism. [21] With this in mind, we decided to analyze the low-frequency part of the vibrational spectra of the NCFs.…”
Section: Low-frequency Molecular and Lattice Vibrations In Dysprosiummentioning
confidence: 93%